Cluster Analysis and Network Visualization of Global Research on Digital Libraries during 2016–2020: A Bibliometric Mapping. Issue 3 (3rd July 2022) - Borgohain, Dhruba Jyoti; Zakaria, Sohaimi; Kumar Verma, Manoj
ABSTRACT: The paper aims at examining the global trends in digital library research based on data extracted from the Scopus database at the global, national, institutional and individual levels. Using performance indicators like total citations, the number of publications, h-index, total link strength the study aims to evaluate the prolific authors, organizations, countries, chronological growth of literature, document forms, most prolific journals, application of Lotkas's law to evaluate the author productivity and analysis of keywords to know the trending topics of research in Digital Libraries. The study uses VOSviewer to prepare the network map of organizational and country co-authorship analysis with clustering technique and MS-Excel for graphical and statistical analysis. The core findings are like the most productive year is 2019 and the number of publications increased rapidly from the starting year of data collection 2016. The results reveal that the USA is the most productive country in terms of the number of publications and impact with the University of Illinois the first rank in the list of prolific institutions. B Gipp from the University of Wuppertal is the most productive author.